A physicochemical study of ophthalmological vital dyes: From dimerization equilibrium in buffer solution to their liposomal dispersions. (March 2019) - Di Nezza, Francesca; Zeppa, Lucio; Costagliola, Ciro; Bufalo, Gennaro; Ambrosone, Luigi
Abstract: Vital dyes are used both in intra-operative and diagnostic ophthalmology as liquid solutions wherein dyes self-associate reducing their effects. Hence, an efficient dyes-delivery system is required to carry the maximum fraction of dye administered to the target site. In this study primarily two aspects of indocyanine green, patent blue V and brilliant blue G have been investigated. First, band profiles of UV–Vis absorption and emission spectra, acquired as a function of dye concentration in buffer solutions(pH = 7.4), have been analyzed to calculate the dimerization constant. Results demonstrate that their self-assembly properties have to be correlated to the molecular polarization. Second, the vital dyes have been loaded into liposomes prepared with the thin-film hydration method followed by extrusion. Encapsulation efficiency has been calculated to be 30%. Scanning electron microscopy and dynamic light scattering measurements have revealed that dye inclusion reduces the liposome diameter. Activation energy of liposome diffusion has been extracted by Arrhenius plots. Zeta potential measurements as a temperature function have been exploited to evaluate a dimensionless surface charge and prove that ratio charge(dye-loaded liposome)-to-charge(blank liposome) is always greater than unity and decreases with temperature. Highlights: Association properties of Indocyanine Green, Patent Blue and Brilliant Blue in buffer solutions were performed. Indocyanine Green, Patent Blue and Brilliant Blue loaded in liposomal dispersions were performed. A SEM investigation shows that dye-liposomes exhibit a size less than blank-liposomes. Dynamic light scattering measurements suggest that blank liposomes have the highest diffusion activation energy. Z-Potential measurements indicate that the charge on surface liposomes decreases with the temperature.